PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MASA PANDEMI COVID-19 DI KELAS V SD NEGERI 066043 MEDAN HELVETIA T.A 2020/2021 - Panggabean, Ruth Donda; Lumbantobing, Panni Ance; Farida, Niken; Natalia, Ita Tiurlan (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
The purpose of this study is to determine the teacher’s role in increasing student learning interest during COVID-19 pandemic and factors that supporting and inhibiting. This research is descriptive qualitative. The data collection techniques were interviews and questionnaires while the data analysis techniques were data reductions, data display and drawing conclusions. Respondents in this study were a teacher and 21 students at state elementary school 066043 Medan Helvetia. The results of this study indicate that the teacher’s role in increasing student interest in learning during the covid-19 pandemic at state elementary school 066043 Medan Helvetia, were: teachers as mentors, teachers as motivators, teachers as evaluators and teachers as learning resources.